2D and 3D stability analysis of tunnel roof collapse in stratified rock: A kinematic approach. (December 2017) - Qin, Changbing; Chian, Siau Chen
Abstract: This paper aims to predict the potential roof collapse of deep tunnels subjected to water table level changes and deterioration of rock overlying the tunnel crown. The effect of partly weathered rock masses is represented with lower mechanical parameters. Meanwhile, the pore water pressure is taken as external loads acting on the rock bank below the water table without consideration of capillary effect. Under the combined effects of the above two conditions, a novel and comprehensive failure mechanism is postulated for analyses of roof stability of tunnels. Both two-dimensional (2D) and three-dimensional (3D) collapse mechanisms formed by multi-surfaces are proposed in kinematic analyses where upper bound solutions of the failure mechanism are derived based on variational principle and stepwise optimization technique. Validation of the proposed approach is carried out which showed consistencies of failure mechanisms with analytical and numerical results presented in published literatures. Parametric studies with rectangular and circular tunnel cross-sections are also conducted in 2D and 3D analyses so as to depict the effect of weathered parameters and pore water on incipient falling blocks. The output from these parametric studies could potentially provide useful reference for engineers in the design and construction of deep-buried tunnels. Highlights: Partly weathering and varying water table level lead to occurrence of combined failure. 2D and 3D failure mechanisms are proposed for kinematic analyses of combined roof collapse. Variational principle and stepwise optimization are used to derive the upper bound solutions. Parametric studies are carried out for specific cases of deep rectangular and circular tunnels.